Frail older individuals maintaining a steady standing position: Associations between sway measurements with frailty status across four different frailty instruments - Schuelein, Samuel; Sieber, Cornel; Gaßmann, Karl-Günter; Ritt, Martin (Clinical Interventions in Aging, 2020)
Objective: An analysis of the relationships between static equilibrium parameters and frailty status and/or severity across four different frailty measures. Design: Cross-sectional analysis. Setting: Geriatric wards of a general hospital. Participants: One hundred twenty-three geriatric inpatients comprising 70 women (56.5%) and 53 men (42.7%) with an age range of 68–95 years. Methods: The variation in the center of pressure (CoP), ie, the length of sway, the area of sway, and the mean speed, was assessed for different positions/tasks: 1) wide standing with eyes open (WSEO); 2) wide standing with eyes closed (WSEC); 3) narrow standing with eyes open (NSEO) and 4) narrow standing with eyes closed (NSEC), using a force plate. Frailty status and/or frailty severity were evaluated using the frailty phenotype (FP), the clinical frailty scale (CFS), the 14-item frailty index based on a comprehensive geriatric assessment (FI-CGA), and a 47-item frailty index (FI). Results: WSEO length of sway (FP, CFS, FI-CGA, FI), WSEO area of sway (FP, CFS, FI-CGA, FI), and WSEO mean speed (FP, CFS, FI-CGA, FI), WSEC length of sway (FP, FI-CGA, FI), WSEC area of sway (FP, FI-CGA, FI) and WSEC mean speed (FI-CGA, FI), NSEO length of sway (FP, FI-CGA, FI), NSEO area of sway (FP, CFS, FI-CGA, FI), and NSEO mean speed (FP, CFS, FI-CGA, FI), NSEC length of sway (FI-CGA, FI), NSEC area of sway (FI-CGA, FI) and NSEC mean speed (FI-CGA, FI) were associated with the frailty status and/or severity across the four different frailty instruments (all p < 0.05, respectively). Conclusion: Greater fluctuations in CoP with increasing frailty status and/or severity were a uniform finding across various major frailty instruments.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Balance quality parameters; Frailty instruments; Older people